Sovereignty in the Province of Mariquita in the Context of the Early Latin American Republics, 1808-1816 (2024)
The construction of Latin American republics in the 19th century demanded a rethinking of the democratic notions of representation, people, and sovereignty. Modern constitutionalism provided a novel significance to the concept of popular sovereignty that was quickly assimilated by the independence fighters. The objective is to examine the foundations, subjects, and implications of sovereignty in the province of Mariquita (New Granada), 1808-1816. Through the historical-conceptual analysis of the political landscape, this perspective explores the meanings, contradictions, and limits of local sovereignty, starting from a diverse documentary corpus. In the process, it was observed that the sovereignty adopted by the Republic of Mariquita had as its reference French constitutionalism and the Hispanic legal tradition, but developed its own notion that included a triple conceptual foundation. In conclusion, the province’s sovereignty presented a political-conceptual convergence between the legal framework of the Spanish administration and the imprint of modern constitutionalism.